Characteristics of the Marine Atmospheric Boundary Layer Over the Southern Ocean in Response to the Synoptic Forcing. Issue 15 (3rd August 2018) - Lang, F.; Huang, Y.; Siems, S. T.; Manton, M. J.
Abstract: The characteristics of the marine atmospheric boundary layer (MABL) in relation to synoptic meteorology over the Southern Ocean are examined using upper‐air soundings and surface precipitation at Macquarie Island (54.62°S, 158.85°E), with a primary focus on the post‐cold‐frontal environment where large cloud and radiative biases are presented in a multitude of climate models. Thermodynamic profiles from the European Centre for Medium‐Range Weather Forecasts ERA‐Interim reanalyses are compared with the observations to evaluate their representation of the MABL characteristics. Observations confirm that boundary layer clouds over the Southern Ocean commonly reside within a shallow MABL under the influence of frequent midlatitude cyclones and fronts. The evaluation of MABL height shows that, for both observations and reanalysis, the inversion is higher northward of the low center and under postcold front conditions. Under cold frontal passages, however, the main inversions are not well represented by ERA‐Interim, which is featured by an underestimate of the MABL height by 22%. Significant differences are found in the moisture profiles within the MABL between the observations and ERA‐Interim soundings within the context of cold frontal passages. The moisture in the ERA‐Interim is found to be too confined to the surface layer, which is consistent with the shallower MABL represented by the ERA‐Interim. Analysis of the surface precipitation shows that ERA‐Interim overestimates the amount of precipitation over Macquarie Island in the vicinity of cyclone cores but underestimates the precipitation not immediately associated with cold fronts, leading to an overall underestimate of the annual precipitation by 11%. Key Points: Climatology of the marine boundary layer in response to the synoptic forcing over the Southern Ocean Identification of biases in the ERA‐Interim reanalysis